Ingroup and outgroup effects on party Placement perceptions - Mauerer, Ingrid Doris; Puy-Segura, María Socorro (Cambridge University Press, 2025)
How do identities affect our political perceptions? Drawing on the social identity theory, we offer a new notion and empirical modeling strategy to study divergence in party placement perceptions. Our framework builds on the idea that membership in social groups has the potential to act as a social identity by systematically structuring perceptual divergence among groups. We conceptualize two consequences of social identity formation, ingroup favoritism and outgroup hostility: an ingroup effect brings a party closer to the preferred policy of the group; an outgroup effect pushes the party away. The approach permits detecting these effects and pinpoints the group-based characteristics producing perceptual polarization in multiparty systems using standard public opinion survey data. An application to the Basque region of Spain shows that over two decades, social identities around national sentiments and religion have produced the most perceptual divergence and polarization, whereas gender or social class do not structure party perceptions in the region.
Keywords: Identidad colectiva; Polarización (Ciencias sociales); Social identities; Identity politics; Perceptions; Ingroup-outgroup; Divergence